Distinct polymer-dependent sorption of persistent pollutants associated with Atlantic salmon farming to microplastics - Abihssira Garcia, Isabel Sofia; Kögel, Tanja; Gomiero, Alessio; Kristensen, Torstein; Krogstad, Morten; Olsvik, Pål Asgeir (Marine Pollution Bulletin, 2022)
publishedVersion